Adjuvant Rosa Damascena has a Small Effect on SSRI-induced Sexual Dysfunction in Female Patients Suffering from MDD - Farnia, V.; Hojatitabar, S.; Shakeri, J.; Rezaei, M.; Yazdchi, K.; Bajoghli, H.; Holsboer-Trachsler, E.; Brand, S. (Pharmacopsychiatry, 2015)
Background: Treating major depressive disorders (MDD) with selective serotonin-reuptake inhibitors (SSRIs) may impact negatively on sexual function. On the other hand, a satisfying sexual life is associated with overall life satisfaction. Therefore, managing this negative side effect of SSRIs may have an important role in the treatment of MDD. In a former study, adjuvant Rosa damascena oil improved sexual dysfunction in male patients suffering from both MDD and SSRI-induced sexual dysfunction (SSRI-I SD). The aim of the present study was to test whether the same pattern of results would be observed among female patients suffering from both SSRI-I SD and MDD.Method: In a double-blind, randomized and placebo-controlled clinical trial, a total of 50 female patients (mean age: 34 years) treated with an SSRI and suffering from MDD and SSRI-I SD were randomly assigned either to the verum (Rosa damascena oil) or to the placebo condition. Patients completed self-ratings of depression and sexual function at baseline, 4 weeks later, and at the end of the study 8 weeks after its start.Results: Sexual desire, sexual orgasms, and sexual satisfaction increased over time. Patients in the verum group reported decreased pain. Overall sexual score increased in the verum as compared to the placebo condition.Conclusions: Whereas in male patients suffering from both MDD and SSRI-I SD adjuvant Rosa damascena oil improved sexual function, data on female patients are less robust and suggest only modest effects on female sexual function.
Keywords: major depressive disorder (MDD); female patients; rosa damascena oil; sexual dysfunction; serotonin-reuptake inhibitors (SSRIs); SSRI-induced sexual dysfunction